1979
DOI: 10.1113/jphysiol.1979.sp012628
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic innervation of the locus coeruleus from the dorsal raphe and its action on responses to noxious stimuli.

Abstract: SUMMARYThe connexions between the dorsal raphe nucleus and the nucleus locus coeruleus were studied in urethane anaesthetized rats.1. (Cells in the locus coeruleus gave an excitatory response to a noxious stimulus, e.g. leg pinch.2. This excitatory response was blocked by either a parenteral or an ionophoretic injection of morphine and recovered after an injection of naloxone.3. Electrical stimulation in the region of the dorsal raphe blocked excitatory locus coeruleus responses to noxious stimuli.4. While nal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(56 citation statements)
references
References 29 publications
4
52
0
Order By: Relevance
“…Patients had LHb rsFC to the DRN that have been linked to serotoninergic functions. Our results revealed a unique Hb rsFC for patients with CRPS to brainstem structures that have not been previously linked to the Hb, for example, the LC, PBN, and NCS, all of which have repeatedly been associated with pain processing and pain modulation (Leichnetz et al 1978;Segal 1979;Cechetto et al 1985). These functional connections, together with altered Hb rsFC to the rest of the brain, may contribute to spontaneous, ongoing pain in patients.…”
Section: Hb Rsfc In Patients With Crpsmentioning
confidence: 83%
“…Patients had LHb rsFC to the DRN that have been linked to serotoninergic functions. Our results revealed a unique Hb rsFC for patients with CRPS to brainstem structures that have not been previously linked to the Hb, for example, the LC, PBN, and NCS, all of which have repeatedly been associated with pain processing and pain modulation (Leichnetz et al 1978;Segal 1979;Cechetto et al 1985). These functional connections, together with altered Hb rsFC to the rest of the brain, may contribute to spontaneous, ongoing pain in patients.…”
Section: Hb Rsfc In Patients With Crpsmentioning
confidence: 83%
“…In addition, the LC is a strategically situated nucleus, located where the noradrenergic and the serotonergic systems establish a close functional relationship. The LC receives dense 5-HT projections coming from dorsal raphe and pericoerulear 5-HT neurons (Segal, 1979). Interestingly, it has been suggested that LC neurons are subject to the indirect influence of 5-HT 1A receptors (Szabo and Blier, 2001c).…”
mentioning
confidence: 99%
“…It is well established that locus coeruleus (LC) NE neurons modulate the 5-HT system, and evidence is accumulating for a major influence of 5-HT on the NE system (see Haddjeri et al, 1997;Kaehler et al, 1999). The LC receives dense 5-HT projections coming from dorsal raphe and pericoerulear 5-HT neurons (Aston-Jones et al, 1991;Kaehler et al, 1999), which exert an inhibitory role (Léger and Descarries, 1978;Segal, 1979). This is supported by the observation that lesioning 5-HT neurons with a 5-HT neurotoxin produced a marked elevation of firing rate of NE neurons (Haddjeri et al, 1997).…”
mentioning
confidence: 99%